2020
DOI: 10.1039/d0cp01274b
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-induced structural transformations and new polymorphs in BiVO4

Abstract: BiVO4 exhibits a rich structural polymorphism under high pressure where both fergusonite- and zircon-type BiVO4 transform to scheelite and β-fergusonite structures upon compression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 43 publications
3
21
2
Order By: Relevance
“…In our previous research on ABO 4 compounds, such as BiVO 4 , 38,39 ZrGeO 4 40 and LaVO 4 , 41 it is believed that different polymorphic compounds will finally transform into the same high-pressure structure if the pressure is high enough. For example, the fergusonite-and zircon-type BiVO 4 finally transform into the same scheelite-BiVO 4 at high pressure.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous research on ABO 4 compounds, such as BiVO 4 , 38,39 ZrGeO 4 40 and LaVO 4 , 41 it is believed that different polymorphic compounds will finally transform into the same high-pressure structure if the pressure is high enough. For example, the fergusonite-and zircon-type BiVO 4 finally transform into the same scheelite-BiVO 4 at high pressure.…”
Section: Resultsmentioning
confidence: 99%
“…The most relevant changes (highlighted with asterisks in Figure ) are the appearance of two extra peaks on the left and right side of the (101) peak of scheelite, the broadening of the strong peak at 2θ ≈ 8°, and the emergence of additional peaks at higher angles. To try to explain the XRD of the PS phase, we have considered the structures previously reported in the literature, that is, different monoclinic structures described by space groups C 2/ c and P 2 1 / n . However, none of them (alone or in coexistence with scheelite) can account for all observed peaks.…”
Section: Resultsmentioning
confidence: 99%
“…At 523(1) K and ambient pressure, fergusonite-type BiVO 4 undergoes a transition to a tetragonal scheelite-type polymorph (space group I 4 1 / a ). , Hydrostatic pressure reduces the transition temperature , and makes it possible to induce the fergusonite–scheelite transition by compression at room temperature (RT) . It is known that the zircon-type polymorph also transforms under compression into the scheelite-type polymorph. , The structural stability of the scheelite-type phase has been also studied. , There is an agreement in the fact that this polymorph suffers a phase transition near 20 GPa. However, two different monoclinic structures have been proposed for the post-scheelite (PS) phase. , This discrepancy needs to be clarified .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pressure has been regarded as an effective synthesis method to access new structures or novel properties of materials. Recently, it has been reported that both fergusonite-BiVO 4 and zircon-BiVO 4 would transform to scheelite-BiVO 4 under pressure. It is interesting to note that the latter transition is irreversible, which will transform back to fergusonite-BiVO 4 rather than the original zircon-BiVO 4 after pressure release. Therefore, it can be described as a zircon-to-scheelite-to-fergusonite phase transition in a compression-decompression cycle for pure zircon-BiVO 4 .…”
Section: Introductionmentioning
confidence: 99%